The impact of digital workplace spirituality on innovative work behavior among millennial workers: The moderating role of digital skills - Suhada, Suhada; Diantoro, Aris Kusuma; Jannah, Annisa Wardatul; Valya, Riska; Trianti, Dwi (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2024)
This study investigates how digital workplace spirituality (DWS) influences innovative work behavior (IWB) among employees, with a focus on the moderating role of digital skills (DS) amid ongoing digital transformation in the post-pandemic era. Using a quantitative survey approach, the research involved 250 millennial remote workers in Sleman Regency and Yogyakarta City. Data analysis employed Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that DWS significantly and positively impacts IWB. Additionally, DS positively influences DWS and acts as a moderator in the DWS-IWB relationship. However, DS does not directly affect IWB. These results highlight the vital role of digital skills in enhancing workplace spirituality and fostering innovative behavior. Introducing DS as a novel construct in the DWS-IWB relationship provides new insights into workplace spirituality, especially in digital contexts. Public interest statements The article will provide valuable insights into applying a holistic approach that can offer a competitive advantage and ensure that your organization is well-positioned to thrive and innovate in an increasingly complex world.